PENGARUH RELIGIUSITAS DAN PENGETAHUAN TERHADAP INTENSI KONSUMEN MUSLIM UNTUK MEMBELI PRODUK KOSMETIK HALAL DENGAN SIKAP SEBAGAI VARIABEL INTERVENING (Studi Kasus Mahasiswa Kota Malang) - Sarrah Nikmatul Hidayah; Maslichah Maslichah; Junaidi Junaidi (Fakultas Ekonomi dan Bisnis Universitas Islam Malang, 2022)
This study aims to determine the effect of religiosity and knowledge on the attitudesand intentions of Muslim consumers to buy Halal cosmetic products. The type ofresearch used is research with a quantitative approach. Based on the results ofresearch conducted by research by distributing questionnaires to students of theIslamic banking study program 18 Malang Islamic University and students of theIslamic economic law study program 18 Islamic State University of Malang. Theresearcher got 207 respondents based on gender, study program, institution and howto find out halal and haram laws with the Maghrib concept. sampling of this researchusing Explanatory Research. The analytical tool used is Amos. The results of thestudy prove the first, that the religiosity variable (X1) has a positive and significantinfluence on the attitude variable (Y1). the second, the knowledge variable (X2) has apositive and significant effect on the Attitude variable (Y1). the third, the religiosityvariable (X1) has a positive and significant influence on the consumer intentionvariable (Y2). the fourth is that the knowledge variable (X2) has a positive effect onthe consumer intention variable (Y2) but the effect is not significant. and the fifthvariable attitude (Y1) has a positive and significant influence on the variableconsumer intentions (Y2).